KEBIJAKAN PEMUNGUTAN RETRIBUSI PASAR PELITA BANGKO KABUPATEN ROKAN HILIR TAHUN 2011-2013 - Melka Martha Yingga; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research present describe the implementation of Bangko markets retribution policy in Rokan Hilir Regency in 2011-2013. Market retributions have purpose to increase a devisa of Agency that based on district regulation Number 21 in 2011 about market service in Rokan Hilir Agency. But until now implementation of Bangko markets retribution policy in Rokan Hilir Regency are not effectively. The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Rokan Hilir Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of Clean, Park and Market Agency, Head of Unit Retribution Clean, Park and Market Agency, staff of retribution and seller in Bangko Markets. The conclution of this research are the implementation of Bangko markets retribution policy in Rokan Hilir Regency are have done by extensivication policy with increase of market, increase of controlling by staff of retribution. Some factors that cause are low of staff and intensif, low of socialization and controlling by Clean, Park and Market Agency, so many illegal seller and low of attention seller to pay the market retributions. Keywords: implementation, policy, retributions and market.